EVOLUTION OF CRISPR SYSTEM AND THEIR APPLICABILITY TO GENOME EDITING IN BACTERIA - Iustin Tiberius Tiberius Munteanu (Journal of Experimental and Molecular Biology, 2022)
Recombinant DNA and genetic engineering technologies have made it possible to manipulate and carry out important advances in biology. However designing reliable, safe and accurate system for genome editing in prokaryotes and eukaryotes has been an issue for a long time. Enzymes (such as polymerases, ligases, and restriction endonucleases) and the polymerase chain reaction (PCR) provided ways to isolate genes and gene fragments, as well as to introduce mutations into gens in vitro, in cells and in a model organism. Today, the field of biology is undergoing a transformative phase with the advent of easy genome engineering using RNA-programmable CRISPR-Cas9. The CRISPR-Cas9 system is an immune system present in prokaryotes that allows the identification of exogenous DNA or RNA molecules. The Cas9 endonuclease is associated with a guide RNA molecule (RNAg) that allows it to form base pairs with target DNA or RNA sequencing, allowing Cas9 to introduce a site-specific double-strand break. Thanks to this breakthrough in genetic engineering Doudna Jennifer and Charpentier Emmanuelle were awarded the Nobel Prize in Chemistry in 2020 (Doudna and Charpentier., 2014). In what follows I will talk about the applicability of this system to edit bacterial genomes by punctiform, genetic and metabolic modifications.